Significance of the clay mineral distribution in the fluvial sediments of the Neogene Himalayan Foreland Basin (central Nepal) - Huyghe, Pascal; Guilbaud, Romain; Bernet, Matthias; Gajurel, Ananta Prasad (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1293 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.100